Therapy-related leukemia: clinical characteristics and analysis of new molecular risk factors in 114 adult patients (Hematology Meeting Reports, 2009)
We studied the clinical characteristics of 114 patients with therapy-related leukemia or therapy related myelodysplastic syndrome (t-Leuk/MDS). The mean age of the patients was 48 years. The Hematological malignancies were the most common primary (53%), followed by breast and ovarian cancer (30% combined). The mean latency until the development of t-Leuk/MDS was 45.5 months. Median survival was 10 months. Cytogenetics was abnormal in 89% of the patients. FLT3 internal tandem duplications were found in six of 41 (14.6%) patients, of whom four had an abnormal karyotype